Reduction in Diabetes-Induced Craniofacial Defects by Maternal Immune Stimulation - Hrubec, Terry C. (Birth Defects Res B Dev Reprod Toxicol, 2006)
BACKGROUND: Maternal diabetes can induce a number of developmental abnormalities in laboratory animals and humans, including facial deformities and defects in neural tube closure. The incidence of birth defects in newborns of diabetic women is approximately 3–5 times higher than among non-diabetics. In mice, non-specific activation of the maternal immune system can reduce fetal abnormalities caused by diverse etiologies, including diabetes induced neural tube defects. This study was conducted to determine whether non-specific maternal immune stimulation could reduce diabetes-induced craniofacial defects as well. METHODS: Maternal immune function was stimulated before streptozocin (STZ) treatment by maternal footpad injection with Freund’s complete adjuvant (FCA), maternal intraperitoneal (i.p.) injection with granulocyte-macrophage colony-stimulating factor (GM-CSF), or maternal i.p. injection with interferon-γ (IFNγ). Streptozocin (200 mg/kg i.p.) was used to induce hyperglycemia (26–35 mmol blood glucose) in female ICR mice before breeding. Fetuses from 12–18 litters per treatment group, were collected at Day 17 of gestation. RESULTS: Craniofacial defects were observed in fetuses from all hyperglycemic groups. The incidence of defects was significantly decreased in fetuses from dams immune stimulated with IFNγ or GM-CSF. The most common defects were reduced maxillary and mandibular lengths. Both were prevented by maternal stimulation with GM-CSF. CONCLUSION: Maternal immune stimulation reduced the incidence of diabetic craniofacial embryopathy. The mechanisms for these protective effects are unknown but may involve maternal or fetal production of cytokines or growth factors that protect the fetus from the dysregulatory effects of hyperglycemia.